A comparative evaluation of cetane enhancing techniques for improving the smoke, NOx and BSFC trade-off in an automotive diesel engine. (1st April 2021) - Chacko, Nivin; Johnson, Clinton; Varadarajan, Premnath; Sai Srinivas, Sajja; Jeyaseelan, Thangaraja
Graphical abstract: Highlights: Rendered a comprehensive outlook on the cetane improving techniques. Examined the engine combustion, emission characteristics with hydrogenation and EHN addition. Ignition delay and premixed burn fraction reduced significantly compared to diesel. Partial hydrogenation provided better smoke-NOx-BSFC trade-off. Abstract: The cetane number of a fuel strongly influences the combustion parameters and the emission characteristics of a diesel engine. In the case of biodiesel, the presence of polyunsaturated fatty acid methyl ester lowers the cetane number and leads to the decrement in ignition quality. This study investigates the potentiality of two different cetane enhancing techniques, viz. partial hydrogenation and addition of 2-Ethylhexyl nitrate (EHN) to improve the combustion quality of a diesel–biodiesel (B20) blend without hindering the emissions trade-off. The karanja biodiesel used here is exposed to partial hydrogenation in an autoclave reactor and the change in fuel composition is analyzed with gas chromatography. 2-Ethylhexyl nitrate (EHN) is chosen as the cetane enhancer with a concentration of 2000 ppm blended in B20. The NOx, smoke, and brake specific fuel consumption trade-off are quantified for diesel, B20, partially hydrogenated biodiesel blend (HB20), and EHN blended (B20 + EHN) fuels. An improvement in trade-off is observed with the use of modified B20 fuels at mid-range engine loads; however, the base diesel outperformed B20 and its modified forms at full load operations. Overall, the partial hydrogenation is proven to be a more beneficial method to improve the biodiesel trade-off characteristics than the addition of EHN.